Factors affecting maternal serum magnesium levels during long-term magnesium sulfate tocolysis in singleton and twin pregnancy - Nakazawa, Hiroshi; Uchida, Akiko; Minamitani, Tomoyuki; Makishi, Aya; Takamatsu, Yukou; Kiyoshi, Kenji; Samoto, Takashi; Funakoshi, Toru (The journal of obstetrics and gynaecology research, 2015)
Aim Our aim was to determine factors that affect maternal serum magnesium (Mg) levels, to help ensure the safety and efficacy of long‐term magnesium sulfate (MgSO4) therapy for threatened preterm labor in singleton and twin pregnancies. Material and Methods We retrospectively and arbitrarily studied 100 patients (singleton pregnancy, n = 65; twin pregnancy, n = 35) who received i.v. MgSO4 for >48 h for tocolysis of threatened preterm labor. We used multiple regression analysis to investigate the functional relations between the candidate factors and maternal serum Mg levels. Results MgSO4 was administered as a loading dose of 3 g for 1 h followed by a maintenance dose of 1.0–2.0 g/h. There were no maternal severe adverse events related to the elevated Mg levels in any of the subjects. The results of multiple regression analysis revealed that total dose of MgSO4 for 24 h before blood collection (g/day), total serum protein level (g/dL), serum total calcium level (mg/dL), serum creatinine level (mg/dL) and maternal bodyweight (kg) significantly affected maternal serum Mg levels in both singleton and twin pregnancies (all P‐values were < 0.001). Gestational age (weeks) and period of MgSO4 administration (days) at blood collection had no significant effect in singleton or twin pregnancies. Conclusion Our study statistically shows that dose of MgSO4, total serum protein level, serum total calcium level, serum creatinine level and maternal bodyweight are key factors to achieving safe and effective long‐term tocolysis with MgSO4 in not only singleton but also twin pregnancies.